The Gender of Authorship: Heiner Müller and Christa Wolf - Helen Fehervary (Studies in 20th & 21st Century Literature, 1980)
The relationship between sexuality and politics has always been an underlying assumption of the avant-garde. In recent East German avant-garde literature, the notion of authorship as production has become associated with technological rationality and the patriarchal socialist state. The ensuing crisis of the traditional male author has thus led necessarily to a radicalization of subjectivity and to the politics of gender. A comparison of two contemporary texts, one by a female author, one by a male, shows that the crisis of authorship assumes two distinctly different forms when differences in gender are taken into account. The East German authors Heiner Müller and Christa Wolf have exhibited remarkably similar literary and political developments. Two of their most recent texts, Mülller's Hamletmachine and Wolf's No Place. Nowhere, both address the problematic of traditional male authorship and the disintegration of a preconceived literary gender identity. Yet, these two texts exemplify very different assumptions about the relationship between authorship and the literary tradition. Müller's text suggests the imprisonment of the male author within a petrified system of tradition and images, and hence the necessity of deconstruction. Wolf's text manifests a process of creating a new form of female-identified authorship and the possibility of redefining the tradition of literature and its future.
Keywords: sexuality; politics; East German avant-garde; authorship; patriarchal socialist state; patriarchal; socialist state; politics of gender; gender; female author; East German author; Heiner Müller; Christa Wolf; Hamletmachine; " No Place. Nowhere" literary gender identity; gender identity; female-identified; deconstruction